Relations of fine-root morphology on 137Cs uptake by fourteen Brassica species. (December 2015) - Aung, Han Phyo; Aye, Yi Swe; Mensah, Akwasi Dwira; Omari, Richard Ansong; Djedidi, Salem; Oikawa, Yosei; Ohkama-Ohtsu, Naoko; Yokoyama, Tadashi; Bellingrath-Kimura, Sonoko Dorothea
Abstract: Fourteen Brassica species consisting of seven leafy vegetables and seven root vegetables were examined for 137 Cs uptake differences in relation to their fine-root morphological characters. A pot experiment was conducted from November 2014 to February 2015 in a Phytroton using a contaminated soil of Fukushima prefecture. Leafy vegetables showed bigger root diameters, larger root surface area and larger root volume. Consequently, leafy vegetables had higher 137 Cs uptake compared to root vegetables. Among the three fine-root parameters, only root surface area was observed as a significant contributing factor to higher 137 Cs uptake in terms of transfer factor (TF, dry weight basis). Kakina exhibited higher 137 Cs TF value (0.20) followed by Chinese cabbage (0.18) and mizuna (0.17). Lower TF values were observed in turnip (0.059), rutabaga (Kitanoshou) (0.062) and radish (Ha daikon) (0.064). Highlights: Leafy vegetables showed larger fine-root parameters than root vegetables. Leafy vegetables had higher 137 Cs uptake than root vegetables. Only root surface area contributed towards higher 137 Cs uptake.